A comprehensive study of the degradation of aqueous monoethanolamine solution during CO2 capture from power plant flue gases : analytical techniques, degradation kinetics, degradation prevention techniques - Teeradet Supap (Chulalongkorn University, 2014)
Thesis (Ph.D) -- Chulalongkorn University, 2007